The effects of S-nitrosoglutathione on intestinal ischemia reperfusion injury and acute lung injury in rats: Roles of oxidative stress and NF-κB. (June 2018) - Turan, Inci; Sayan Ozacmak, Hale; Ozacmak, V. Haktan; Barut, Figen; Ozacmak, I.Diler
Highlights: GSNO treatment attanuated I/R induced intestinal injury and lung injury. GSNO treatment reduced oxidative stress and neurophil accumulation. GSNO inhibited iNOS and NF-κB expression in reperfused intestine tissue. Abstract: Background: Intestinal ischemia and reperfusion (I/R) induces oxidative stress, inflammatory response, and acute lung injury. S-nitrosoglutathione (GSNO), a nitric oxide donor, has been documented to have protective effects on experimental ischemia models. Aim: The aim of this study was to examine the effect of GSNO on I/R-induced intestine and lung damage and detect the potential mechanisms emphasizing the protective role of GSNO. Methods: Intestinal I/R was induced by occluding the superior mesenteric artery for 30 min followed by reperfusion for 180 min. GSNO was administered intravenously before reperfusion period (0.25 mg/kg). The levels of lipid peroxidation, reduced glutathione, and myeloperoxidase (MPO), histopathological evaluation and immunohistochemical expressions of both nuclear factor KappaB (NF-κB) and inducible nitric oxide (iNOS) in intestine and lung tissues were assessed. Results: Histolopathologic evaluation demonstrated that intestinal I/R induced severe damages in the intestine and the lung tissues. Histopathological scores decreased with GSNO treatment. GSNO treatment reduced lipid peroxidation and MPO levels and inhibited expression of NF-κB and iNOS in the intestine. Conclusion: Our results suggest that GSNO treatment may ameliorate the intestinal and lung injury in rats, at least in part, by inhibiting inflammatory response and oxidative stress.